Microgels for Cell Delivery in Tissue Engineering and Regenerative Medicine - Xuan, Leyan; Hou, Yingying; Liang, Lu; Wu, Jialin; Fan, Kai; Lian, Liming; Qiu, Jianhua; Miao, Yingling; Ravanbakhsh, Hossein; Xu, Mingen; Tang, Guosheng (Nano-Micro Letters, 2024)
Microgels prepared from natural or synthetic hydrogel materials have aroused extensive attention as multifunctional cells or drug carriers, that are promising for tissue engineering and regenerative medicine. Microgels can also be aggregated into microporous scaffolds, promoting cell infiltration and proliferation for tissue repair. This review gives an overview of recent developments in the fabrication techniques and applications of microgels. A series of conventional and novel strategies including emulsification, microfluidic, lithography, electrospray, centrifugation, gas-shearing, three-dimensional bioprinting, etc. are discussed in depth. The characteristics and applications of microgels and microgel-based scaffolds for cell culture and delivery are elaborated with an emphasis on the advantages of these carriers in cell therapy. Additionally, we expound on the ongoing and foreseeable applications and current limitations of microgels and their aggregate in the field of biomedical engineering. Through stimulating innovative ideas, the present review paves new avenues for expanding the application of microgels in cell delivery techniques. Highlights: 1 This review provides a comprehensive summary associated with recent progress in the preparation and application of microgels. 2 The characteristics and applications of microgels and microgel-based scaffolds for cell culture and delivery are elaborated with an emphasis on the advantages of these carriers in cell therapy. 3 This review expounds on the ongoing and foreseeable applications and current limitations of microgels and their aggregate in the field of biomedical engineering. 4 Through stimulating innovative ideas, the present review paves new avenues for expanding the application of microgels in cell delivery techniques.